2017
DOI: 10.1002/mnfr.201700223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated gastrointestinal digestion and fermentation on polyphenolic content and bioactivity of brown seaweed phlorotannin‐rich extracts

Abstract: Although phlorotannins, TP levels and antioxidant power of the extracts were strongly reduced after in vitro digestion and fermentation, their anti-genotoxic activity and cell growth inhibitory effect in colon HT-29 cells was maintained and enhanced. HMW was the most effective fraction, indicating that the high molecular weight phlorotannins potentially exert a stronger beneficial effect in the colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 54 publications
(111 reference statements)
2
47
0
Order By: Relevance
“…Seaweeds are rich in phenolic compounds with varied bioactive properties [46,47]. Rajauria et al [48] identified and characterized eight phenolic compounds from brown Irish seaweed Himanthalia elongate, which exhibited strong antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…Seaweeds are rich in phenolic compounds with varied bioactive properties [46,47]. Rajauria et al [48] identified and characterized eight phenolic compounds from brown Irish seaweed Himanthalia elongate, which exhibited strong antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…Another study separated the small (< 2 kDa) phlorotannins from Ascophyllum nodosum on a C18 column into two distinct peaks using diode array detector (DAD) . However, separation and identification of phlorotannins by HPLC fitted with a DAD is complicated even further by the lack of standards available for comparison . Whilst DAD detection can be useful for analysis of compounds with similar molecular weights but different electronic distribution in the chromophore, leading to different UV spectra, standards or literature data are needed for comparison if the compounds are to be identified.…”
Section: Liquid Chromatography Of Phlorotannins and Hyphenated Technimentioning
confidence: 99%
“…Several reports indicated that polyphenolic compounds extracted from natural materials including plants have anti-genotoxic properties (Corona et al, 2017;Surh & Ferguson, 2003;Williams, Dashwood, Hendricks, & Bailey, 1989). These reports indicated that the polyphenolic components scavenge free radicals from the cells and consequently protect the cellular systems from oxidative damage.…”
Section: Introductionmentioning
confidence: 99%